Green innovation on firm value with financial performance as mediating variable: Evidence of the mining industry - Rina Yuniarti; Noorlailie Soewarno; Isnalita (Asian Academy of Management Journal, 2022)
The topic of environmental performance is gaining much attention from academics and politics when it is associated with each country’s policies regarding environmental problems. Unfortunately, the comprehensive studies to observe this case become rare, therefore this study is aimed to investigate the direct and indirect effect of green innovation on firm value based on financial performance as the mediating variable. Mining companies which participate in Corporate Performance Rating Assessment (PROPER) listed in the Indonesia Stock Exchange during the year of 2012–2018 were used as the samples. The financial performance was measured by return on assets (ROA) and the firm value were measured by Tobin’s Q. The results showed that green innovation had a positive effect on firm value. Financial performance has a positive effect on firm value and financial performance mediates the effect of green innovation on firm value. The green innovation could increase the mining company value. This increase is mediated by financial performance. This present study has been conducted to reveal the direct and indirect effect of green innovation and firm value, financial performance, and firm value comprehensively in which never been done before.